Pembangunan Sistem Informasi Manajemen Peserta Praktik Kerja Lapang berbasis Web dengan Framework Laravel menggunakan Metode RAD (Studi Kasus: PT. Indonesia Power UP Suralaya) - Andi Rosadi; Faizatul Amalia; Djoko Pramono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Internship is an activity that held in PT Indonesia Power UP Suralaya regularly supposed to look for competent prospective workers according to a company standard. Furthermore, the internship is a synchronization process between educational program in school or college of mastering the skill throughout the work activity directly. Welcoming the street vendor acceptance, the preparation begins by making an agreement on the amount of capacity each division and informing the capacity to the street vendor. Nevertheless, some trouble found is a quota submission flow conventionally which is the person in charge directly comes to the division provided. In addition, there is no any quota information yet for the internship participants. The internship participant management is committed manually, such as providing the internship participant letter, identity card, inputting the score and certification distribution. Therefore, the research is conducted by supposed to solve those troubles and produce the information system for managing the internship participant using framework laravel. Rapid Application Development is the expansion to start. As a result, the system produces 51 functional needs tested by using unit testing and validation produced valid in each test case. Non-functional necessity testing gets two, using sortsite application for compatibility as a result that system could be used for determined web browser. User Acceptance Test (UAT) is also done for each task given with a 100% result.